Atractyloside Levels in Xanthium strumarium and Atractyloside Concentrations in the Serum of Rats Given Xanthium strumarium - Ozturk, Yasin; Keskin, Zeliha; Tanyildizi, Sadettin; Gul Baykalir, Burcu; Korkak, Fatih Ahmet; Dagoglu Hark, Betul; Dagoglu, Gurdal (Kafkas Univ, Veteriner Fakultesi Dergisi, 2021)
Atractyloside (ATR) may cause severe liver and kidney damage. However, there is a lack of information about levels of ATR in parts of Xanthium strumarium and the concentrations and kinetics of ATR in the serum. In this study, we determined atractyloside levels in Xanthium strumarium parts, its serum concentrations and some kinetic parameters concerning time with the gas chromatography-mass selective (GCMS) method. After administering (80 mg/kg ATR) X. strumarium seed extract to rats through gastric gavage, blood samples were collected at the 0th, 4th, 6th, 8th, 12th, 24th, 36th, 48th, 60th, 72nd, 96th, and 120th h. After extraction, hydrolysis and derivatization of the plant and serum samples were analyzed by the GC-MS instrument. The ATR level in the X. strumarium seeds was 3.043 mg/g in August, 3.502 mg/g in September and 3.800 mg/g in October. ATR was not detected in other parts of the plant. After ATR administration to rats, the C-max, value of ATR was calculated as 10.77 mu g/mL at T-max. of 48 h and t(1/2 )of 6.07 h. A thorough understanding of ATR circulation in the blood will aid in determining the course of its toxic effects in the bloodstream, the onset of symptoms and the general management plan for ATR poisoning. Moreover, the results obtained from this study will contribute to the antidote studies for ATR poisoning.
Xanthium strumarium’da Atraktilozid Seviyeleri ve Xanthium strumarium Verilen Sıçanların Serumunda Atraktilozid Konsantrasyonları
Keywords: Atractyloside; GC-MS; Rat; Serum; Xanthium strumarium L.